Deterioration of groundwater quality in the vicinity of an active open-tipping site in West Malaysia - Rahim, Bahaa-eldin.E.A.; Yusoff, I.; Samsudin, A.R.; Yaacob, W.Z.W.; Rafek, A.G.M. (Springer Verlag (Germany), 2010)
There is an urgent need for characterization of leachate arising from waste disposal to ensure a corresponding effective leachate management policy. Field and laboratory studies have been carried out to investigate the impact of municipal landfill leachate on the underlying groundwater at a site in West Malaysia. The solid waste was disposed of directly onto an unprotected natural soil formation. This situation was made worse by the shallow water table. The hydrochemical composition of groundwater in the vicinity of the site (background) is a dilute mixed cation, bicarbonate water. The high ionic balance error of similar to 13.5% reveals that the groundwater body underneath the site was a highly contaminated leachate rather than contaminated groundwater. Elevated concentration of chloride (355.48 mg/L), nitrate (10.40 mg/L as NO(3)), nitrite (14.59 mg/L), ammoniacal-N (11.61 mg/L), sodium (227.56 mg/L), iron (0.97 mg/L), and lead (0.32 mg/L) measured downgradient indicate that the contamination plume has migrated further away from the site. In most cases, the concentration of these contamination indicators, together with the ranges of sodium percentage (66.3-89.9%) and sodium adsorption ratio (10.1-19.7%), were found to be considerably higher than the limit values of safe water for both domestic and irrigation purposes, respectively.